2012
DOI: 10.1016/j.jana.2011.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Influences on Antiretroviral Therapy Adherence Among HIV-Infected Puerto Ricans

Abstract: Adherence to antiretroviral therapy (ART) is integral to the successful treatment of HIV infection. Research has indicated that HIV-infected Latinos may have difficulty adhering to ART. While studies have demonstrated strong relationships between numerous psychosocial factors and ART adherence, no research has examined if cultural factors are also involved in ART adherence among Latinos. Our study examined the relationship between acculturation to mainstream U.S. culture, bicultural self-efficacy, and ART adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Studies focusing on other domain-specific self-efficacy measures reported a positive link between adherence and self-efficacy in patient-physician interactions [ 147 , 148 ], coping self-efficacy [ 149 ], bi-cultural self-efficacy [ 150 ], self-efficacy for managing negative mood, adhering to medication, symptoms and fatigue management, communicating with health care providers and getting support from others [ 151 ]. Self-efficacy when disclosing drug use to providers and for safer drug use were not as effective predictors of self-reported adherence as adherence self-efficacy [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies focusing on other domain-specific self-efficacy measures reported a positive link between adherence and self-efficacy in patient-physician interactions [ 147 , 148 ], coping self-efficacy [ 149 ], bi-cultural self-efficacy [ 150 ], self-efficacy for managing negative mood, adhering to medication, symptoms and fatigue management, communicating with health care providers and getting support from others [ 151 ]. Self-efficacy when disclosing drug use to providers and for safer drug use were not as effective predictors of self-reported adherence as adherence self-efficacy [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of interest was the fact that both traditional machismo and caballerismo were significantly related to medication adherence in the multivariate model, even with the presence of variables which previously have been found to be associated with medication adherence among people living with HIV, such as depression (Kalichman and Grebler 2010); alcohol use (Broyles et al 2011; Chandler 2011; Kalichman et al 2012); time since diagnosis (van Servellen and Lombardi 2005), health care-related barriers (Murphy et al 2000) and acculturation (Robbins et al 2012). Only one other variable, higher medication side effects, was found to be associated with a lower likelihood of medication adherence, consistent with previous research (Ammassari et al 2001; Applebaum et al 2009; Muchomba et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A study of 17 HIV-positive Puerto Rican adults living in the USA examined the association between ART adherence and acculturation and bicultural self-efficacy (the ability to effectively navigate both cultures in which one lives) (Robbins et al 2012). Higher adherence to ART was associated with greater acculturation to both US mainstream culture and Latino culture, as well as bicultural efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…In this preliminary trial we could not control for differences in baseline factors such as participants in the treatment arm being more likely to have a partner. This and other factors such as acculturation levels may influence the outcome of an intervention and might be explored in future research [60]. …”
Section: Discussionmentioning
confidence: 99%